La lealtad de los estudiantes de la Universidad Nacional de Chimborazo, Riobamba – Ecuador - Saltos Aguilar, Wilson (2017)
The research work refers to the services perceived by the students of the National University of Chimborazo, to know the causes and levels of loyalty, identifying the risk factors and success of the quality of educational services. The loyalty forecast is based on the following components: Tangible Elements, Responsiveness, Empathy, Reliability, and Safety, (Servqual Model), responding to this constant need to improve to achieve the frequency distribution of levels of cognitive loyalty , Conative, affective and action; Students who distinguish quality educational services.